A Risk Prediction Score for Renal Replacement Therapy in Critically Ill Septic - Acute Kidney Injury Patients - Filipe Marques; José Agapito Fonseca; Joana Gameiro; João Gouveia; José António Lopes (Publicações Ciência e Vida, 2022)
Introduction: Acute kidney injury (AKI) is a major complication in critically ill septic patients and is associated with increased morbidity and mortality. A recent study suggested a risk score based on patient's chronic comorbidities and acute events at intensive care unit (ICU) admission as a reliable tool for predicting AKI in critically ill adult population. The aim of this study was to adapt this score to septic-AKI patients and evaluate its prognostic value as predictor of the need for renal replacement therapy (RRT) at ICU admission. Methods: This is a retrospective analysis of 399 septic-AKI patients admitted to the Division of Intensive Medicine of the Centro Hospitalar Universitário Lisboa Norte between January 2008 and December 2014. The Kidney Disease Improving Global Outcomes (KDIGO) classification was used to define AKI. The Renal Replacement Therapy Risk Score was adapted from the AKI risk prediction score proposed by Malhotra et al (Nephrol Dial Transplant. 2017;32:814-22). Results: Fifty two percent of patients were KDIGO stage 3, 25.8% KDIGO stage 2 and 22.3% KDIGO stage 1. Twenty seven percent of patients required RRT. Patients requiring RRT had higher risk score than those who did not (6.6±2.5 vs 5.1 ±2.6, p<0.001). An optimal cut-off value of ≥ 6 in this score predicted the need for RRT with sensitivity 0.630 and specificity 0.391. Conclusion: The RRT risk score at ICU admission was independently associated with the requirement of RRT septic-AKI patients. The assessment of this ratio is simple and can prove useful in identifying patients at risk for need of RRT.